SOCIAL NETWORKS OF THE INTERNET WITHIN THE THEORY OF AUTOPOIESIS BY NIKLAS LUHMANN - E. Yudina; S. Zakharova (Вестник университета)
The social networks existing for centuries as social communities in family and companionship, achieved new opportunities of self-updating and public expression with the emergence of the Internet and formation social networks in it. To reveal features of each of these phenomena authors give two definitions of social network. One of them characterizes the social network as a special social community, another emphasizes specifics of social networks of the Internet. By consideration of network interaction in the Internet as a social system authors are guided by the concept of an autopoiesis of N. Luman. Within the social networks of the Internet, according to authors, there is an autopoesis, spontaneous and self-making system which depends on information transfer in the course of interaction between members of network. The system of social networks of the Internet unlike mass media exists due to interpersonal communications. Privacy, personal information is its language and a cultural code.